The Shape Shifter - Hillerman, Tony (New York Harper Collins Publishers, 2006)
Retired Police Lieutenant Joe Leaphorn returns to put together the clues from his last unsolved case--a mystery involving the disappearance of a priceless Navajo rug--without the help of Jim Chee and Bernie Manuelito, who are on their honeymoon.
Keywords: a